Theorizing Relations in Indigenous South America. Issue 2 (1st June 2019) - Gálvez, Marcelo González; Di Giminiani, Piergiorgio; Bacchiddu, Giovanna
Abstract : Once conceptualized as self-evident connections between discrete social units systematized through ethnographic fieldwork, relations are being increasingly treated as instantiations of local ontological theories. The ethnography of indigenous South America has provided a source of inspiration for this analytical shift. As manifested in the contributions to this special issue, at the core of indigenous practices and discourses on relations lies a tension between 'dependence on otherness' and an 'ethics of autonomy'. In this introduction, we revisit this tension by focusing on the 'taming of relations', a process through which subjects attempt to maintain the autonomy of each being vis-à-vis their relational constitution dependent on others. We argue that rather than being a necessary condition, autonomy is always a partial outcome of relations linking human and non-human others.